THE EFFECT OF GOOD CORPORATE GOVERNANCE (GCG) MODERATION ON A CORRELATION BETWEEN FUNDAMENTAL FACTORS TO THE DIVIDEND POLICY - agustrisna, juwita (International Journal of Public Budgeting, Accounting and Finance, 2018)
The research objective is to analyze the influence of moderation of the Good Corporate Governance (GCG) on the correlation among fundamental factors (liquidity, leverage, profitability, sale growth, firm size, operation of cash flow, profit volatility, capital expenditure, and detained profit) simultaneously and partially on dividend policy in non-financial companies. The population was 376 non-financial companies listed in the Indonesia Stock Exchange from 2009 to 2013. The samples were 20 companies with 100 units of analysis selected based on purposive sampling method. The data were analyzed by using the multiple-linear regression analysis and the residual test with an SPSS software program. The research result proved that simultaneously fundamental factors (liquidity, leverage, profitability, sale growth, firm size, operation of cash flow, profit volatility, capital expenditure, and detained profit) did not influence dividend policy in non-financial companies. Partially, all independent variables did not influence significantly dividend policy. Good Corporate Governance variable was the moderation variable which significantly strengthened fundamental factors with dividend policy of non-financial companies.